PENERAPAN MODEL PROBLEM BASED INTRUCTIONS (PBI) UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KEALAS V NEGERI 009 KEPENUHAN - Rejeki Rejeki; Abdul Putra Ginda Hasibuan; Rinja Efendi (STKIP ROKANIA, 2021)
This study aims to determine that the application of the Problem Based Intruction (PBI) learning model to improve student learning outcomes in thematic subjects in grade V SD Negeri 009 Kepenuhan. The background of this study is the unmet achievement of the learning objectives illustrated from the students' daily test scores on the thematic learning of 20 students only 8 students who achieved the KKM, while 12 more students were doing remedial activities, the KKM set was 75. The subjects receiving the action in this study is the fifth grade students of odd semester 009 Elementary School in Kepenuhan in the 2020 academic year of 20 students consisting of 8 male students and 12 female students. The data analysis technique used is the model of collecting several instruments in the form of student and researcher activity sheets and question sheets. The results of this study were seen from the first cycle of the first meeting as many as 11 students 55% who reached the KKM. In the first cycle the second meeting also increased again, as many as 13 students 65%. In the second cycle of the first meeting it is known that student learning outcomes have increased again from 20 students 15 (75%) students have reached the KKM. At the second meeting the students' learning outcomes were very satisfying, from 20 students 18 (90%). The conclusion of this study is that the application of the Problem Based Intruction (PBI) learning model to improve student learning outcomes in thematic subjects in grade V SD Negeri 009 Kepenuhan succeeded.